PERILAKU LENTUR PERBAIKAN BALOK BETON BERTULANG DENGAN VARIASI LEBAR CARBON FIBRE REINFORCED POLYMER - Atika Ulfah Jamal; Helmy Akbar Bale; Iqbal Haqiqi (TEKNISIA, 2015)
The retrofitting of reinforced concrete structural elements required in case of material degradation which results in decreased strength, stiffness, stability and resistance to environmental conditions. One material that can be used to retrofit concrete structures is the Carbon Fibre Reinforced Polymer (CFRP). Experimental research must be done toward the influence of CFRP width variations to retrofit reinforced concrete beam flexural capacity after damage. The specimen used for this research is a beam with 15x20x120 cm3 dimension. There were three beams used and divided into two groups, Control Beam (BK) and Carbon Beam (BC). These three beams were given a load until the first crack then had to retrofit with CFRP, and was given a load again upon the beams finally fallout and  the result of maximal load that able to be supported by the beam is obtained.  The research result shows that there is the significant increase in the beam flexural strength. The wider CFRP used for retrofitting, the greater beam flexural capacity increases. CFRP uses as retrofitting material in the beam bending area also able to prevent a new crack in the bending area.